Epidemiology of football (soccer) injuries in the 2012/2013 and 2013/2014 seasons of the Italian Serie A - Falese, L.; Della Valle, P.; Federico, B. (Research in Sports Medicine, 2016)
Epidemiological studies on football (soccer) injuries are needed to assess both the magnitude of the problem and the effectiveness of preventive programmes. However, few data are available for Italy, which hosts one of the main football leagues in Europe. In this study, we aimed to describe the epidemiology of football injuries in the 2012/2013 and 2013/2014 seasons of the Italian Serie A. Information about injury location, type, date of occurrence and duration of absence was obtained from www.football-lineups.com, a free collaborative international database on football. Overall, 363 injuries occurred throughout the two seasons affecting 286 players. The most commonly reported injuries were thigh-strain and knee injury, which accounted for 42% and 19% of all injuries, respectively. Injury incidence increased with age and was particularly higher from August to October. Results suggest that injury prevention strategies should be introduced from the preseason to reduce the risk of injuries, especially muscle strains.